Microbial and Chemical Shelf‐Life of Vacuum Steam‐Pasteurized Whole Flaxseed and Milled Flaxseed. Issue 2 (19th January 2018) - Shah, Manoj; Eklund, Bridget; Conde Lima, Luiz Gustavo; Bergholz, Teresa; Hall, Clifford
Abstract : Abstract: Flaxseed is an oilseed with many health benefits. Flaxseed may be consumed raw or in processed form. In the raw form, there is a potential for microbial contamination. Several pasteurization methods have been used to reduce microbial contamination. However, such treatments may affect chemical properties of foods. In this study, vacuum steam‐pasteurization was conducted on whole flaxseed and milled flaxseed using 4 different conditions (3 min at 75 °C, 3 min at 90 °C, 9 min at 90 °C, and 3 min at 105 °C). Microbial and chemical shelf‐life was monitored for 28 wk (36 wk for aerobic plate counts). Significant reduction ( P < 0.05) in microbial counts (total aerobic plate counts, and yeast and mold counts) occurred after pasteurization and during storage of both whole flaxseed and milled flaxseed. Although both the moisture content and a w increased after pasteurization, they were similar to the unpasteurized samples during storage. Peroxide value, free fatty acid, headspace volatiles, fatty acid profiles, oil content, and secoisolariciresinol diglucoside (SDG) content were chemical indices measured. Only small changes were observed in the chemical indices after vacuum steam‐pasteurization for both pasteurized whole flaxseed and milled flaxseed as compared to the unpasteurized flaxseed at most instances. Vacuum steam‐pasteurization can be used as a safe alternative for the microbial reduction of low‐moisture products, such as flaxseed, without significantly affecting chemical stability. Practical Application: Vacuum steam‐pasteurization can be effectively used for the treatment of whole flaxseed and milled flaxseed to reduce spoilage microorganisms, such as total aerobes and yeasts and molds. In addition, this pasteurization method had minimal effects on several chemical shelf‐life parameters with positive impact on SDG of the processed flaxseed.